2002
DOI: 10.1038/nature00846
|View full text |Cite
|
Sign up to set email alerts
|

The C2B Ca2+-binding motif of synaptotagmin is required for synaptic transmission in vivo

Abstract: Synaptotagmin is a synaptic vesicle protein that is postulated to be the Ca(2+) sensor for fast, evoked neurotransmitter release. Deleting the gene for synaptotagmin (syt(null)) strongly suppresses synaptic transmission in every species examined, showing that synaptotagmin is central in the synaptic vesicle cycle. The cytoplasmic region of synaptotagmin contains two C(2) domains, C(2)A and C(2)B. Five, highly conserved, acidic residues in both the C(2)A and C(2)B domains of synaptotagmin coordinate the binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
365
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 315 publications
(397 citation statements)
references
References 28 publications
24
365
2
1
Order By: Relevance
“…Genetic knockouts of SYT1 result in dramatic suppression of evoked release in several model organisms (Bellen, 1999;Sudhof and Scheller, 2001). Of the two C2 domains, mutagenesis of C2B has a more severe effect on the SYT-controlled fast synchronous release (Fernandez-Chacon et al, 2001;Mackler et al, 2002;Robinson et al, 2002). In Drosophila melanogaster, a single mutation of tyrosine to asparagine in the C2B domain severely disrupts calcium-triggered exocytosis (Yoshihara and Littleton, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic knockouts of SYT1 result in dramatic suppression of evoked release in several model organisms (Bellen, 1999;Sudhof and Scheller, 2001). Of the two C2 domains, mutagenesis of C2B has a more severe effect on the SYT-controlled fast synchronous release (Fernandez-Chacon et al, 2001;Mackler et al, 2002;Robinson et al, 2002). In Drosophila melanogaster, a single mutation of tyrosine to asparagine in the C2B domain severely disrupts calcium-triggered exocytosis (Yoshihara and Littleton, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We herein demonstrated that this tyrosine residue lies at the interface of the C2B domain with the SNARE helices. The AD3 mutation efficiently disrupts the constitutive SYT interaction with the t-SNARE assembly even in the context of the tandem C2 domains (Figure 8, A and B), providing clear evidence that the C2B domain alone is necessary and sufficient for the constitutive link to the t-SNARE assembly.Mutations of the calcium-binding residues in the C2B domain block evoked release (Mackler et al, 2002), indicating that a further calcium-triggered SYT action is required for efficient exocytosis. A detailed analysis of these mutants revealed a close correlation between the decrease in neurotransmitter release and a reduction in calcium/phospholipid interaction rather than the reported calcium-triggered oli-C. Rickman et al…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A1). Using a polyclonal antibody to the synaptic vesicle protein synaptotagmin I (Mackler et al, 2002), the presynaptic area of the NMJ was readily identified. These results show that synaptotagmin I is highly enriched at the NMJ whereas Flamingo is primarily present on axons.…”
Section: Flamingo Is Expressed In Axons and At Synapsesmentioning
confidence: 99%
“…Following one hour incubation with a blocker solution (2-5% bovine serum albumin, 0.2% Tween-20 in PBS, PBT), the preparation was stained overnight at 4 ÂC using primary antisera, followed by one hour washes with PBT and 1-2 hours incubation with secondary antibodies at room temperature, and visualized using a Nikon fluorescence microscope. The following primary antibodies were used: rat anti-Syb (1:300, Wu et al, 1999), mAb anti-CSP (ab49, 1:20, Zinsmaier et al, 1994), rabbit anti-Syt (1:300, Mackler et al, 2002), mAb anti-Futsch (22C10, 1:100, Developmental Studies Hybridoma Bank), mAb anti-Hiw (6H4, 1:3, Wan et al, 2000), rabbit anti-DAP 160 (1:300, Roos and Kelly, 1999), mAb nc82 (1:20; Wagh et al, 2005), a polyclonal antibody to clathrin heavy chain (1:50) and to LAP (1:200, Zhang et al, 1998), a polyclonal antibody to glutamate receptor III (Marrus et al, 2004), a polyclonal antibody to the Drosophila vesicular glutamate transporter (VGluT, 1:500, Daniels et al, 2004), and a polyclonal antibody to HRP (Jan and Jan, 1982). Fluorescence-conjugated secondary antibodies were used 1:100 (Jackson Immunology Labs).…”
Section: Immunocytochemistry and Microscopymentioning
confidence: 99%